Some recent advances in partial difference equations - Petropoulou, Eugenia (Bentham e Books, 2010)
Lately there is an increasing interest in partial difference equations demonstrated by the enormous amount of research papers devoted to them. The initial reason for this increasing interest was the development of computers and the area of numerical analysis, where partial difference equations arise naturally when discretizing a partial differential equation. The aim of this e-book is to provide some recent advances in the field of partial difference equations. Applications of partial difference equations in numerical analysis and systems theory are also presented. This e-book will be of use t.